ORNAMEN JEPARA SEBAGAI SETRUKTUR BENTUK PADA PENCIPTAAN MEJA KONSUL - Jati Widagdo (SULUH: Jurnal Seni Desain Budaya, 2019)
The consul table as a complementary facility needs a comfortable and aesthetic design, in this case the Jepara ornament is the basic idea of creating a consul table that emphasizes function and aesthetic value.The purpose of making the work is to create a consul table with Jepara ornaments as a form idea for the main, while the goal is to create a consul table in a creative and innovative way. the consul table itself is a complementary space facility The Jepara ornament is a stylization of the shape of the wuni fruit which has a characteristic with the fruit located between the leaves. The Jepara ornament as an ornamental element in the creation of a consul table is a creative and innovative design. The main function of the consul table is, as a decorative table to complement the flexible form space, adding to the decorative value of the space, using a natural color finish that displays the real texture of wood.